Efektivitas Penggunaan Metode Eksperimen Terhadap Hasil Belajar Siswa Kelas V SDN 2 Krandegan Pada Mata Pelajaran IPA Materi Peristiwa dalam Kehidupan - Trisnawati, Oky Ristya (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
The problem in this study is the low activity carried out by students in science learning where learning still focuses students on listening and note-taking activities. This study aims to describe student learning outcomes in the experimental method. The research method used is descriptive with a qualitative approach. The data analysis technique used in this research is the triangulation technique, namely test, observation and documentation techniques. Each data was analyzed using the Miles and Huberman models. The results showed that the average student learning activity in science learning using the experimental method was included in the good category.